The Existence of Islamic Boarding School in The Internalization of Religious Moderation Values: A Systematic Literature Review - Mohamad Erihadiana; Mahmud Mahmud; Rusman Nurdiansyah; Sofwan Gozali; Raka Akhmad Hilman Nurwahyu; Nurjaman Wahyu Ramdani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Religious life in Indonesia faces increasing challenges marked by intolerance, extremism, and digital radicalization within a pluralistic society. Specific Background: Islamic boarding schools (pesantren), as long-established Islamic educational institutions, have historically integrated religious teachings, local wisdom, and national values through holistic educational traditions. Knowledge Gap: Despite extensive discussions on religious moderation, a comprehensive synthesis of empirical evidence on how pesantren internalize religious moderation values remains limited. Aims: This study aims to systematically examine the existence and role of pesantren in internalizing religious moderation values in Indonesia. Results: Based on a Systematic Literature Review of seventeen peer-reviewed articles published between 2021 and 2025, the findings indicate that pesantren internalize religious moderation through epistemological foundations of wasatiyyah, integrative curricula, exemplary kyai leadership, communal daily practices, and adaptive engagement with digital media, contributing to social cohesion and national unity. Novelty: This study presents a consolidated conceptual understanding of pesantren as epistemic, pedagogical, and socio-cultural ecosystems for religious moderation. Implications: The findings highlight pesantren as strategic socio-religious institutions capable of sustaining moderate, inclusive, and tolerant religious life while reinforcing national integrity amid globalization and digital transformation. Highlights: Pesantren operate as holistic educational ecosystems embedding moderation through lived religious and social practices. Integrative curricula, moral leadership, and digital engagement support balanced religious-national identities. Moderation-oriented education within pesantren contributes to social cohesion and protection against radical narratives. Keywords: Islamic Boarding Schools, Religious Moderation, Pesantren Education, National Unity, Systematic Literature Review